Peran Media Sosial dalam Meningkatkan Kunjungan Wisata: Analisis Destinasi Viral di Indonesia - Aulia Rahma Utami; Zikriansyah Ramadhan; Wisnu Sabdo Utomo; Ahman Sya (Jurnal Sains Geografi, 2026)
The digitalization phenomenon has transformed tourism promotion and consumption patterns in Indonesia, but there is still no comprehensive understanding of the mechanisms by which social media influences increased tourist visits. This study aims to analyze the role of social media in increasing tourist visits through a study of viral destinations in Indonesia. The research method uses a qualitative descriptive approach with secondary data collection techniques from scientific publications, tourism statistics, and social media content. The analysis was conducted on several destinations that experienced a surge in popularity after going viral on social media, including content characteristics, platforms used, and their impact on tourist visits. The results show that social media plays a significant role in creating awareness, shaping destination image, and influencing tourist visit decisions. Authentic visual content and user-generated content have proven most effective in increasing destination attractiveness. This study concludes that digital marketing strategies through social media are a crucial instrument in developing Indonesian tourism in the digital era.